2018
DOI: 10.1051/proc/201862139
|View full text |Cite
|
Sign up to set email alerts
|

The Deterministic Evolution Of Illicit Drug Consumption Within a Given Population

Abstract: We study the NERA model that describes the dynamic evolution of illicit drug usage in a population. The model consists of nonusers (N) and three categories of drug users: the experimental (E) category, the recreational (R) category and the addict (A) category. Two epidemic threshold terms known as the reproduction numbers, R0 and µ are defined and derived. Sensitivity analysis of R0 on the parameters are performed in order to determine their relative importance to illicit drug prevalence. The local and global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Recently, the deterministic NERA models of Dauhoo et al (2013) and Badurally Adam et al (2015) were revisited and were further analysed in Ruhomally et al (2018). In the latter work, the authors derived two reproduction numbers, R 0 and μ, which were used to analyse the stability of the system.…”
Section: Mathematical Modelling Of Illicit Drug Consumptionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, the deterministic NERA models of Dauhoo et al (2013) and Badurally Adam et al (2015) were revisited and were further analysed in Ruhomally et al (2018). In the latter work, the authors derived two reproduction numbers, R 0 and μ, which were used to analyse the stability of the system.…”
Section: Mathematical Modelling Of Illicit Drug Consumptionmentioning
confidence: 99%
“…Sensitivity analysis was conducted on the parameters of R 0 and the calculated sensitivity indices were used to scrutinise the model. In the work of Dauhoo et al (2013), Badurally Adam et al (2015), and Ruhomally et al (2018), the models give rise to a recreational-addict free state, which may not always happen in reality. That is, it is not quite possible to have a population free of recreational users and addicts in a given society.…”
Section: Mathematical Modelling Of Illicit Drug Consumptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mathematical modelling of illicit drug consumption. The dynamical study of this social issue can be found in [1], [3], [7], [11], [12], [21], [25] and [23]. However, it must be pointed out that in all these works, the dynamics of the evolution of consumption of illicit drug, under the influence of the social interactions, which are responsible for the drug use spread within drug users community has not been taken into account.…”
mentioning
confidence: 99%